2010
DOI: 10.1245/s10434-010-1488-z
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induces Notch2-Mediated Apoptosis and Suppression of Neuroendocrine Markers in Medullary Thyroid Cancer

Abstract: Background-Currently, complete surgical resection is the only curative option for MTC. Previous work has shown the Notch pathway is a potent tumor suppressor in MTC and that Resveratrol activates the Notch pathway in carcinoid cancer, a related NE malignancy. In this study, we hypothesized that the effects observed on carcinoid cells could be extended to MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 28 publications
(45 reference statements)
1
33
0
Order By: Relevance
“…Resveratrol affects Notch signaling at the transcriptional and post-transcriptional levels (affecting the proteolytic cleavagedependent nuclear translocation and activation). It has been shown that resveratrol induces Notch-2 mRNA expression and promotes profound growth inhibition and apoptosis in medullary thyroid cancer cells (17) and human GI carcinoid BON cells (8). It has also been shown that resveratrol represses Notch-1 activation in human T-cell acute lymphoblastic leukemia MOLT-4 cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol affects Notch signaling at the transcriptional and post-transcriptional levels (affecting the proteolytic cleavagedependent nuclear translocation and activation). It has been shown that resveratrol induces Notch-2 mRNA expression and promotes profound growth inhibition and apoptosis in medullary thyroid cancer cells (17) and human GI carcinoid BON cells (8). It has also been shown that resveratrol represses Notch-1 activation in human T-cell acute lymphoblastic leukemia MOLT-4 cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that resveratrol can trigger NOTCH2-dependent apoptosis. 38 Among differentially regulated proteins, we identified BAX, which is able to lead to mitochondria membrane permeabilization, 39 to be phosphorylated on S72, presumably by CK2, in response to resveratrol but not spermidine. Moreover, the stress-responsive apoptosis signaling activator PAK2 was phosphorylated on S141 in response to spermidine but not resveratrol.…”
Section: Phosphorylation Dephosphorylationmentioning
confidence: 92%
“…Resveratrol, a polyphenolic compound found in grapes, red wine, purple grape juice, peanuts, and some berries, induces apoptosis in part by inhibiting Notch and PI3K/AKT in T-ALL cells (Cecchinato et al, 2007) and in glioblastoma cells (Lin et al, 2011). Recently, it has been reported that resveratrol can also activate Notch2 as a mechanism of apoptosis induction in medullary thyroid cancer (Truong et al, 2011) and in carcinoid (Pinchot et al, 2011). Notch2 may function as a Notch1 antagonist due to its lower transcriptional activity.…”
Section: Strategies To Target the Notch Signaling Pathwaymentioning
confidence: 99%